Determination of protein structures using distance constraints - Samur, Başak. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1998., 1998)
Constraints of different types are applied to a protein chain of 30 residues by using a low resolution model adopted from the cooperative kinematics (CK) model of polymers. The aim was to investigate the importance of the location and number of the distance restraints in reducing the conformational space accessible to the chain. Initially, one constraint is applied to the chain ends. Then, the place of the constraint is changed to the middle of the chain. It was observed that the place of the constraint is very important in the formation of the tertiary structure. also, the effect of applying a constraint between two residues which are close to each other along the chain is investigated. At the second stage of calculations, the number of constraints is increased to two, and the results confirm that increasing the number of constraints effectively restricts the conformational space. A helical protein, referred to as the Rop dimer, is explored as a last case by applying three different distance restraints, which are originally calculated from the real distances of alpha-carbons in the protein Databank structure. The resulting lowest energy conformation showed that a real protein structure can also be predicted with a reasonable accuracy level by using a limited number of distance restraints.
Keywords: Proteins -- Structure.; Polymers.